[Afisz. Incipit] Odczyt Ks. Hodorowskiego majora W.P. ... (Tczew : [wydawca nieznany], 1947)
Afisz informujący o odczycie, 1947 rok.
Keywords: Tczew (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1990.